2018
DOI: 10.1080/14786419.2018.1531407
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids from the roots of Leontopodium longifolium and their inhibitory activity on NO production in RAW264.7 cells

Abstract: Phytochemical investigation of the roots of Leontopodium longifolium, led to the isolation of a novel norsesquiterpene, named as longifolactone (1), along with three known diterpenes. The structures of these compounds were elucidated by analysis of HR-ESI-MS, UV, IR and 1D and 2D NMR spectroscopic data. The absolute configuration of the new compound was determined by electronic circular dichroism (ECD) using both experimental and calculated ECD spectra. Furthermore, their antiinflammatory effects were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay was used to detect LL-3 (chemical structure as shown in Figure 1) [26] cytotoxicity in SH-SY5Y cells. According to Figure 2B, dosage 2.5-20 µM that showed no significant alternation compared to control cells were adopted to detect the LL-3 neuroprotective role in amyloid beta peptide [25][26][27][28][29][30][31][32][33][34][35] )-induced cytotoxicity in SH-SY5Y cells. As Figure 2C shows, LL-3 reversed the cytotoxic activity caused by Aβ [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Effect Of Ll-3 and Amyloid Beta Peptide 25-35 On Cell Viabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay was used to detect LL-3 (chemical structure as shown in Figure 1) [26] cytotoxicity in SH-SY5Y cells. According to Figure 2B, dosage 2.5-20 µM that showed no significant alternation compared to control cells were adopted to detect the LL-3 neuroprotective role in amyloid beta peptide [25][26][27][28][29][30][31][32][33][34][35] )-induced cytotoxicity in SH-SY5Y cells. As Figure 2C shows, LL-3 reversed the cytotoxic activity caused by Aβ [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Effect Of Ll-3 and Amyloid Beta Peptide 25-35 On Cell Viabilitymentioning
confidence: 99%
“…The assay showed that SH-SY5Y cells treated with Aβ 25-35 alone caused great elevation of ROS production compared to the control group. LL-3 significantly reduced the ROS level with G-mean at 2.5 µM (0.49), 5 µM (0.44), 10 µM, (0.39), 20 µM (0.31) ( Figure 3A), implying that LL-3 may relieve oxidative stress induced by Aβ [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Effect Of Ll-3 On Aβ 25-35 -Induced Cellular Reactive Oxygenmentioning
confidence: 99%
See 3 more Smart Citations